2019
DOI: 10.4038/jrrisl.v99i0.1887
|View full text |Cite
|
Sign up to set email alerts
|

Poverty alleviation through improvement in technical efficiency in the smallholder rubber sector: case study from Kegalle District of Sri Lanka

Abstract: Growth and development of the agriculture sector play an important role in the alleviation of poverty. There is a long-lasting debate on whether improvement in efficiency levels leads to eradicate poverty. Further, some studies unveiled that farm and farmer characteristics have a significant influence on poverty. Hence, this study attempts to examine the relationship between technical efficiency and poverty and the effect of farmer's characteristics on poverty levels among the smallholder rubber farmers in Keg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Iluppalla et al (2020) studied the possibility of replacing a part of the 60 pph of commonly used silica filler imported from Well ink Chemical Co., India used in rubber composite for the manufacture of low-speed castor wheel rubber tread formulations. Ishani and et al (2019) studied the relationship between technical efficiency and poverty and the effect of farmer characteristics on poverty levels among the smallholder rubber farmers in Kegalle District. Even though there is a certain number of studies based on the Sri Lankan rubber industry, various rare studies have been found to observe the Sri Lankan rubber industry depending on the historical angle or grievance approach...…”
Section: Review Of Literature and Theoretical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iluppalla et al (2020) studied the possibility of replacing a part of the 60 pph of commonly used silica filler imported from Well ink Chemical Co., India used in rubber composite for the manufacture of low-speed castor wheel rubber tread formulations. Ishani and et al (2019) studied the relationship between technical efficiency and poverty and the effect of farmer characteristics on poverty levels among the smallholder rubber farmers in Kegalle District. Even though there is a certain number of studies based on the Sri Lankan rubber industry, various rare studies have been found to observe the Sri Lankan rubber industry depending on the historical angle or grievance approach...…”
Section: Review Of Literature and Theoretical Applicationsmentioning
confidence: 99%
“…In their study, Nayanakantha et al (2019) observed the adverse effects of drought and high temperatures on the income generated by the rubber industry in the dry zone. Ishani et al (2019) emphasized the potential of poverty alleviation through enhancements in technical efficiency within the smallholder rubber sector in the Kegalle district. Focusing on leaf fall disease, Fernando et al (2019) conducted an extensive investigation in a rubber plantation located in Padiyathalawa.…”
Section: Justifications For the Selection Of Research Areamentioning
confidence: 99%